Evaluasi User Experience Aplikasi AR Tutorial Yamaha R15 Menggunakan User Experience Questionnaire (UEQ) - Setiabudi Sakaria; Subari Subari; Evy Poerbanintyas (LPPM UBHINUS MALANG, 2025)
This study aims to evaluate the user experience (UX) of an Augmented Reality (AR) application designed as a tutorial medium for introducing components of the Yamaha R15 VVA motorcycle. The evaluation was conducted using the User Experience Questionnaire (UEQ) method, covering six aspects: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The research sample consisted of 30 students who have taken or are currently taking the Human-Computer Interaction course at Universitas Bhineka Nusantara. The analysis results showed that the pragmatic quality had an average value of -0.092 and the hedonic quality 0.108, with an overall score of 0.008, categorized as neutral. The average standard deviation of 0.666 indicates a high level of agreement among respondents. Although the application met some visual and interactive aspects, weaknesses were found in navigation features, usage guidance, and audiovisual support. Reliability testing showed that the UEQ instrument is appropriate for use, with a Cronbach’s alpha value of 0.88 (pragmatic) and 0.77 (hedonic). These results recommend further development in usability aspects and supporting features to enhance the effectiveness of the AR-based technical learning application.